Three new dihydroisocoumarin glycosides with antimicrobial activities from Scorzonera aucheriana. (June 2021) - Erik, İshak; Yaylı, Nurettin; Coşkunçelebi, Kamil; Makbul, Serdar; Karaoğlu, Şengül Alpay
Graphical abstract: Highlights: Three new dihydroisocoumarin glycosides were isolated from Scorzonera aucheriana. Scorzoaucherioside II was identified as a new type of phenol ether dimeric dihydroisocoumarin. Structures of the isolated compounds were elucidated by spectroscopic methods. Iso -scorzopygmaecoside and scorzoaucherioside II showed strong antimicrobial activity against Mycobacterium smegmatis . Abstract: Three new dihydroisocoumarin glycosides ( iso -scorzopygmaecoside, scorzoaucherioside I, and scorzoaucherioside II) together with five known compounds (scorzopygmaecoside, scorzocreticoside II, 3, 5-O-dicaffeoyl- epi -quinic acid, 3, 5-O-dicaffeoylquinic acid, and 3, 4-dihydroxyphenyl caffeate) were isolated from the aerial parts of the Scorzonera aucheriana collected from Sivas province in Turkey. The isolated compounds' structures were elucidated based on NMR ( 1 H, 13 C/APT, COSY, HMBC, HSQC, and TOCSY), UV, FT-IR, and LC-QTOF-MS data. These compounds have been isolated for the first time from S. aucheriana . An antimicrobial assay against ten microorganisms was applied to all isolated compounds. Iso -scorzopygmaecoside, scorzoaucherioside I, and 3, 4-dihydroxyphenyl caffeate showed notable anti-pseudomonal activity. Iso -scorzopygmaecoside and scorzoaucherioside II exhibited strong activity against Mycobacterium smegmatis with MIC values of 25.6 μg/mL and 21.2 μg/mL, respectively.